The Effectiveness Of The Implementation Of The Badminton Long Service Learning Model For Grade V Students In Elementary Schools - Pratama, Budiman Agung; Kholis, Moh. Nur (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
Physical education is a learning process that aims to improve physical fitness, motor skills, and healthy living behaviors. In this context, the long serve technique in badminton is one of the basic skills that are important for students to master. This study aims to develop an effective learning model in teaching long service techniques to grade V students, using a Research and Development (R&D) approach through the ADDIE method. The learning process includes needs analysis, material design, media development, implementation, and evaluation. The results showed that 85% of students achieved the excellent category in long service skills, with 10% good and 5% adequate. This data was obtained from observations and interviews that showed student enthusiasm and the availability of adequate learning media. This study concludes that systematic and structured teaching of basic badminton techniques can significantly improve students' skills. The advice given is that students stay active and focused in learning, and teachers are expected to be able to convey the material clearly to achieve optimal learning goals. This research is expected to make a positive contribution to the development of physical education at the elementary school level.